2010
DOI: 10.1371/journal.pmed.1000286
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Quality of Research into a Single Prognostic Biomarker: A Systematic Review and Meta-analysis of 83 Studies of C-Reactive Protein in Stable Coronary Artery Disease

Abstract: In a systematic review and meta-analysis of 83 prognostic studies of C-reactive protein in coronary disease, Hemingway and colleagues find substantial biases, preventing them from drawing clear conclusions relating to the use of this marker in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(113 citation statements)
references
References 53 publications
2
109
0
2
Order By: Relevance
“…Тем не менее, недавно проведенный анализ 83 исследований выявил множество типов ошибок к сооб-щении данных и публикациях, что делает величину любой независимой связи между вчСРБ и прогнозом у пациентов с СИБС недостаточно определенной, в связи с чем данный показатель не может быть реко-мендован для планового измерения [69].…”
Section: неинвазивные методы исследования сердцаunclassified
“…Тем не менее, недавно проведенный анализ 83 исследований выявил множество типов ошибок к сооб-щении данных и публикациях, что делает величину любой независимой связи между вчСРБ и прогнозом у пациентов с СИБС недостаточно определенной, в связи с чем данный показатель не может быть реко-мендован для планового измерения [69].…”
Section: неинвазивные методы исследования сердцаunclassified
“…In a meta-analysis of 83 prospective studies reporting the association of CRP with death and non-fatal cardiovascular events, the authors found that the quality of the studies was so poor (only two reported a measure of discrimination), with evidence of reporting bias and publication bias, that they were unable to make clinical practice recommendations. 8 Nevertheless, the data suggested that CRP measurements are unlikely to add anything to the prognostic discrimination achieved by considering blood pressure and other clinical factors in this patient group. In another study it was concluded that conventional clinical information provided an effective means of risk-stratifying patients with stable coronary disease awaiting coronary bypass surgery and that additional prognostic information from CRP, measured singly or in combination with other biomarkers, was unlikely to be cost-effective.…”
Section: Circulating Biomarkers In Stable Anginamentioning
confidence: 83%
“…Of the 12 markers measured (including hsCRP and IL-6), hs-CRP was the strongest uni-variant predictor of cardiovascular events, and the only plasma marker predicting risk after adjustment in a multi-variant analysis. This was confirmed in a large meta-analysis of hsCRP as a single biomarker in patients with stable CAD, but the authors concluded that a routine measurement of CRP should not be recommended as a single prognostic biomarker (Hemingway et al, 2010). However, in combination with other biomarkers, hsCRP seems to add significant information to traditional risk factors for CVD, and the value of adding hsCRP to standard risk equations was noted in separate cohorts of asymptomatic (middleaged or elderly) men and women (Lavie et al, 2009b).…”
Section: Possible Links Between Hscrp and Ihdmentioning
confidence: 93%